1977
DOI: 10.1111/j.1445-2197.1977.tb03938.x
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Melanoma: Some Aspects of Pathology and Prognosis

Abstract: This is a report on the periods of survival, and the factors that influence survival, in a series of 509 patients treated for malignant melanoma in the Peter MacCallum Clinic, Melbourne. Not the least of these factors is education of the public and the medical profession in its early recognition, which has greatly improved the prognosis. In this context, it is also firmly believed that whenever possible, one clinician only should be responsible for the total surgical management of any patient suffering from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 3 publications
2
8
0
Order By: Relevance
“…Studies examining the prognosis of regressed, transected tumors resulting from incomplete excision are lacking. Our results validate age, sex, Breslow's thickness, ulceration, and SLN status as prognostic factors for melanoma, and imply that transection, and moreover, lack of visible tumor after transection of a melanoma, do not affect patient survival. Conventional thinking would suggest that positive deep margins are a serious problem, preventing accurate staging.…”
Section: Discussionsupporting
confidence: 72%
“…Studies examining the prognosis of regressed, transected tumors resulting from incomplete excision are lacking. Our results validate age, sex, Breslow's thickness, ulceration, and SLN status as prognostic factors for melanoma, and imply that transection, and moreover, lack of visible tumor after transection of a melanoma, do not affect patient survival. Conventional thinking would suggest that positive deep margins are a serious problem, preventing accurate staging.…”
Section: Discussionsupporting
confidence: 72%
“…In large series of the literature [9,12,14,15,17,19,21,27], the overall sex distribution of malignant melanoma of the skin shows a distinct pre ponderance of females over males, as in the present study.…”
Section: Discussionsupporting
confidence: 49%
“…Females, as a rule, show by far better survival ra tes than males, and the differences afier a few years of follow-up range be tween 8 and 20% [12,22,25,26], In comparison with the literature [2,6,18,19], the present study yields relatively lower overall survival rates for both sexes. This is certainly due to our patient material solely evaluated according to invasive malignant melanomas.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Epstein et al found a more favorable ten-year OS in the biopsy group (65%) as compared to the primary wide excision group (56%) but biopsy was loosely defined as less than optimal or complete surgical excision 9. Ironside et al found a five-year OS rate of 66% in the excision- and 43% in the incision biopsy group but failed to describe the distribution of prognostic factors between both groups 10. Rampen et al also found a worse prognosis for patients after an incision biopsy (14 patients) but the study was small and retrospective 11.…”
Section: Discussionmentioning
confidence: 99%